Implementasi Metode Maqashid Syariah Index Terhadap Kinerja Perbankan Syariah - Agung Wahyudi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2022)
The main objective in this study is to know well how much is the achievement of maqashid sharia in effort to measure the performance sharia banking that is expected in accordance with sharia teachings and benefits to public or the public by paying attention to norms achievement indicators. contained in maqashid sharia, it is expected to be able color the world of work both in the financial and non-financial fields, especially in the field of sharia finance, namely sharia banking. This research uses a descriptive qualitative research type with a normative-judicial approach, supported by library research method basis for transformative critical point of view based on the suitability of Islam the goals of the maqashid sharia index (MSI) Mohammed, Dzuljastri & Taib (2008:53) The author collects and searches for data as references consisting of the web, articles, journals, books, mass media related to the discussion of the maqashid sharia index, then the author examines these reading sources comparison of data and facts in Islamic banks. The results of this study use the maqashid sharia index (MSI) method because it is a unity in the discussion of sharia economics and proves that good sharia banking performance is not only seen from the performance of sharia banking with conventional methods sin general but more to maqashid sharia index. (MSI) as an objective measure of performance in an Islamic banking. The implementation of the maqashid sharia index method performance of sharia banking is in accordance with the indicators contained in the maqashid sharia theory according the concept of Abu Zahrah Tahzibul Fardi (Personal Education), Iqamah al Adl (attainment of justice), Jalb al-maslahah (public interest)